Engagement, conduct of life and dropouts in the Danish vocational education and training (VET) system - Nielsen, Klaus [Verfasser] (My University, 2016)
"This study provides support for the idea that school engagement is a central concept when trying to understand the dropout process. One of the strengths of this concept is that it involves understanding dropping out as a process, rather than as an event. However, the concept of school engagement also presents a number of problems. It tends to be functionalistic in nature: Processes of students' school engagement and disengagement are partly the consequences of institutional initiatives - for example, how teachers act or how the school environment is organised. Furthermore, mainstream dropout researchers formulate the concept of engagement both simplistically and mechanistically by seeing engagement as something that the students possess to varying degrees. Inspired by critical psychology, this study includes a different concept of student engagement: We must take the students' life conduct as the point of departure when approaching their school engagement and decision to drop out. The theoretical claims in the paper are substantiated by empirical results from 160 interviews with vocational educational and training (VET) students in the Danish VET system, and this paper will show how school engagement is closely related to the events in the other contextual settings of students' lives." (Autorenreferat; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; G 1.3.2.2.2 Verlauf (Erfolg / Abbruch); I 2.2.1 Westeuropa; Berufsbildungssystem; Berufsausbildung; Ausbildungsabbruch; Einflussfaktor; Berufsschüler; Lebensgestaltung; Dänemark